Gene expression drives local adaptation in humans - Fraser, Hunter B.

(untitled) (Genome Research, 2013)
The molecular basis of adaptation—and, in particular, the relative roles of protein-coding versus gene expression changes—has long been the subject of speculation and debate. Recently, the genotyping of diverse human populations has led to the identification of many putative “local adaptations” that differ between populations. Here I show that these local adaptations are over 10-fold more likely to affect gene expression than amino acid sequence. In addition, a novel framework for identifying polygenic local adaptations detects recent positive selection on the expression levels of genes involved in UV radiation response, immune cell proliferation, and diabetes-related pathways. These results provide the first examples of polygenic gene expression adaptation in humans, as well as the first genome-scale support for the hypothesis that changes in gene expression have driven human adaptation.